Modelo analítico híbrido para seleção de nós retransmissores em cenários com escoamento de dados - LOPES, Carlos André Barros (2019)
In scenarios of cellular networks with high user density the quality of services tends to be reduced by the interference generated by users’ devices overhead on the base station antenna. In the middle of this, the traffic flow arises whose purpose is to distribute the signal through relay users capable of optimizing data delivery. HAMAT is proposed, a hybrid analytical model that contributes to traffic flow from the selection of ideal relay users. This work presents a hybrid analytical model, called HAMAT, which considers AHP and TOPSIS analytical models for decision making. This analytical model is designed to select optimal relay users during the flow of traffic in cellular networks. HAMAT considers multiple criteria for decision making, such as the QoS metrics: Delay, Flow and Packet Loss, and the spatial metric, Euclidean Distance. The proposal is validated from computational simulations and comparisons with other selection algorithms, taking into account the quality of service, in this context the HAMAT overcame the other algorithms with an improvement in QoS parameters up to 61% in one of the evaluated scenarios.